Formação de docentes universitários e a interface com a Educação Especial: revisão sistemática - Silva, Nathalia Carolina Carrara (Universidade Federal de São Carlos, 2025)
After the 1990s, with the implementation of policies known as inclusive policies, there was an increase in the number of students with disabilities enrolling in Brazilian higher education. This demand justifies the need to examine and study the training of university professors, which, in Brazil, occurs at the postgraduate level. Thus, the general objective of this study is to investigate the pedagogical training of Brazilian university professors to work with students with disabilities, identifying its limitations and contributions to the academic trajectory of these students in higher education. Its specific objectives are: 1. To map academic publications on the pedagogical training of university professors from an inclusive perspective. 2. To identify the guidelines present in these publications for working with students with disabilities. 3. To analyze the contributions and limitations pointed out by the literature in relation to university teacher training. This is a systematic review of the literature, using the digital platforms CAPES Periodicals and SciELO and the UFSCar Institutional Repository, without a time frame, following eight basic steps of searching, storing, and selecting academic publications on the proposed theme. Four articles and one master's thesis, published between 2010 and 2021, were selected. The analyses showed that university teacher training in Brazil still focuses on scientific and technical qualifications, with little attention to pedagogical and inclusive dimensions. The absence of specific legislation to standardize training for working with special education students was identified, as well as weaknesses in initial and postgraduate training in this field. As limitations, the studies point to the lack of teacher preparation, insufficient use of accessible resources, and low participation in continuing education. As contributions, we highlight the structured offer of continuing education in many universities and the growth in the number of special education students in higher education, which has driven the debate and the need for more inclusive practices. It is concluded that it is necessary to strengthen institutional policies that guarantee continuing education, technical and pedagogical support, and practices based on equity and the appreciation of diversity, with a view to consolidating higher education that provides quality services to this population.
University teacher training and its interface with Special Education: a systematic review
Keywords: Educação Especial; Formação de professores; Educação superior; CIENCIAS HUMANAS; 4. Educação de Qualidade